Tailoring microstructure and corrosion behavior of CoNiVAlx medium entropy alloys via Al addition. (October 2022) - Pan, Zhimin; Luo, Hong; Zhao, Qiancheng; Cheng, Hongxu; Wei, Ya; Wang, Xuefei; Zhang, Bowei; Li, Xiaogang
Abstract: The effect of Al addition on the microstructure and corrosion behavior of CoNiVAlx medium entropy alloys (MEAs) was investigated. Results indicated that the enhanced corrosion resistance caused by Al addition might be attributed to the dominant role of Al in stabilizing the passive film. The difference in the Volta potentials of FCC and B2 phases indicated the existence of microgalvanic coupling, which suggested that the B2 phase served as a localized cathode while the FCC matrix and FCC lath acted as anodes. This accounted for the pitting mechanism of CoNiVAlx MEAs via Al addition. Graphical Abstract: ga1 Highlights: Al addition shows positive effects on the corrosion resistance of CoNiVAlx medium-entropy alloys (MEAs). The relationship between the microstructure and corrosion behavior is established. The presence of the B2 phase constitutes the microgalvanic coupling with the FCC matrix and the FCC laths. The pitting mechanism and enhanced corrosion resistance of CoNiVAlx MEAs via Al addition are clarified.